Thursday

May 26, 2016
Posted by **Amy** on Wednesday, January 19, 2011 at 1:20pm.

(4)/(x+2) - (4)/(x)

__________________ = 1

2

- algebra -
**helper**, Wednesday, January 19, 2011 at 2:16pm(4/(x + 2) - 4/x)/2 = 1

rewrite as

(4/(x + 2) - 4/x) * 1/2 = 1

4/(2(x + 2)) - 4/2x = 1

4/(2x + 4) - 4/2x = 1

LCD 2x(2x + 4)

(8x - 4(2x + 4))/(2x(2x + 4)) = 1

multiply both sides by 2x(2x + 4)

8x - 4(2x + 4) = 2x(2x + 4)

8x - 8x -16 = 4x^2 + 8x

-16 = 4x^2 + 8x

4x^2 + 8x + 16 = 0

4(x^2 + 2x + 4) = 0

divide both sides by 4

x^2 + 2x + 4 = 0

Solve this by Quadratic formula or completing the square

I leave the rest to you to solve